Shaking table test on small-scale retrofitted model of Sefid-rud concrete buttress dam. - Ghaemmaghami, A.R (Earthquake engineering & structural dynamics.)
Sefid-rud concrete buttress dam with a height of 106 m was damaged during the devastating 1990 Mamjil earthquake. The dam was repaired and strengthened using epoxy grouting of cracks and the installation of post-tensioned anchors. In a previous study, nonlinear seismic response of the highest monolith with empty reservoir was investigated experimentally through model testing. A geometric scaled model of 1:30 was tested on a shaking table to study dynamic cracking of the model. As a result of the similarity between model and prototype cracking pattern, the model was retrofitted according to prototype retrofitting plan after the Manjil earthquake and re-tested on shaking table to estimate the current safety of the prototype. Experimental test results showed that the post-tensioning resulted in a significant decrease in dynamic responses in terms of crest displacement and measured strains of teh retrofitted model in comparison with its corresponding responses at the first test. No cracking was observed in the retrofitted model when the base motion peak acceleration exceeded a value that was 22 percent higher than the one caused cracking in the first model. This can be interpreted as the efficiency of prototype post-tensioning system in evaluating the seismic safety of Sefid rud dam.